Dilly My Robot Mower / Nurul Aine Musa - Musa, Nurul Aine (2020)
Dilly My Robot Mower is a Malaysia-based company engaged in the development, manufacture and marketing of outdoor power products, cutting equipment for fardening. The company’s product offering robotic lawn mowers. The Company’s operations are divided into three business areas: the Asia business area sells forest, park and garden products to retailers and domestic users. Dilly My Robot Mower company serve a product with the design objective is to come up with a mower that is portable, durable, easy to operate and maintain. machines are utilized to cut and trim grass in lawns and gardens for residential and commercial sectors. In addition, these battery mowers are powered by a rechargeable battery, Each of our clients to ensure that they are able to gather new consumers, spread brand awareness, and increase their revenue.